The Promise of Intercultural Mission - Corrie, John (Transformation, 2014)
‘Intercultural Theology’ began in the 1970’s as a way of expressing theological mutuality and equality between cultures. Since then, the word ‘intercultural’ has gained currency in a number of fields, secular and religious. This article explores the possibilities of speaking of mission as ‘intercultural’ rather than ‘cross-cultural’ as a way of expressing the cultural engagement that is more appropriate to a postmodern world. The inadequacies of the cross-cultural approach, with its roots in modernity, are examined in the light of the complexity and diversity of cultural identities today. Intercultural mission in contrast is relational, mutual, dialogical, open-ended, and creates space within which God’s missio dei can be experienced. Two examples are offered of intercultural mission in practice. It is suggested that this resonates with Bosch’s proposal for a new paradigm for mission in a postmodern context.